Agricultural intensification in Ethiopia: Patterns, trends, and welfare impacts - Berhane, Guush; Abate, Gashaw T.; Wolle, Abdulazize (International Food Policy Research Institute, 2022)
Ethiopia has made substantial efforts in the last three decades to increase agricultural productivity through modern input intensification and stimulate overall economic growth. Despite the high growth rates in recent decade, Ethiopia’s overall intensification and yield levels remained below what is considered optimal. This study examines the patterns, trends, and drivers of agricultural intensification and productivity growth during the recent decade (2012 - 2019) using three rounds of representative household data collected from the four main agriculturally important regions of the country. The descriptive results indicate a positive trend in both the adoption rate and intensity of inputs and output, albeit from a low base compared to other contexts and with considerable heterogeneity by access to information, rainfall levels and variability, labor, soil quality, remoteness, among others. The econometric results show significant association between intensification, yield growth, household dietary diversity (a proxy measure for food and nutrition security), and consumer durables. However, the results on the association between current yield levels and per capita consumption expenditures are mixed (i.e., while an increase in cereal yield only improve food consumption expenditures, an increase in cash crops yield mainly improve non-food consumption expenditures). In sum, while the increasing input intensification and the resulting yield gains are associated with improvement in household diets and consumer durables, it falls short to have strong impact on incomes (as measured by total consumption expenditures), indicating that more efforts have to be made to see meaningful impacts on higher order outcomes. Additional welfare improving productivity gains through increased input intensifications may require investments to put in place appropriate fertilizer blends linked with localized soil nutrient requirements, investments to generate locally suited improved seeds and appropriate mechanisms to reach farmers, ways to mitigate production (rainfall) risk, and investments to remodel Ethiopia’s extension system to provided much needed technical support to farmers on production methods.